Enhancing the quality of transferred single-layer graphene with poly(4-vinylphenol) interlayer on flexible substrates. (20th May 2016) - Choi, Yeonhoi; Chun, Sungwoo; Hong, Ahyoung; Ha, Chunho; Park, Wanjun
Abstract: We report the use of poly(4-vinylphenol) (PVP) as a promising contact surface of transferred graphene, capable of sustaining the original performance found in as-grown graphene. Enhancement of surface tension obtained by O2 plasma treatment of the PVP surface also increases transferred graphene quality. With an easy coating method, PVP can be applied to any flexible substrate as the interlayer to increase transferred graphene quality. Owing to the mechanical flexibility and chemical inertness of PVP, the introduction of a PVP interlayer provides a general method for graphene soft electronics to be integrated into any flexible substrate.